Dramatic increase in sea otter mortality from white sharks in California - M. Tim Tinker; Brian B. Hatfield; Michael D. Harris; Jack A. Ames (Marine Mammal Science, 2016)
Although southern sea otters ( Enhydra lutris nereis ) are not considered prey for white sharks ( Carcharodon carcharias ), sharks do nonetheless bite sea otters. We analyzed spatial and temporal trends in shark bites on sea otters in California, assessing the frequency of shark bite wounds in 1,870 carcasses collected since 1985. The proportion of stranded sea otters having shark bites has increased sharply since 2003, and white shark bites now account for >50% of recovered carcasses. The trend was most pronounced in the southern part of the range, from Estero Bay to Point Conception, where shark bite frequency has increased eightfold. Seasonal trends were also evident: most shark‐bitten carcasses are recovered in late summer and fall; however, the period of elevated shark bite frequency has lengthened. The causes of these trends are unclear, but possible contributing factors include increased white shark abundance and/or changes in white shark behavior and distribution. In particular, the spatiotemporal patterns of shark‐bitten sea otters match increases in pinniped populations, and the increased availability of marine mammal prey for white sharks may have led to more sharks spending more time in nearshore waters utilized by both sea otters and pinnipeds.